PENGARUH PROFITABILITAS, LIKUIDITAS, LEVERAGE, DAN REAL INTEREST RATE TERHADAP FINANCIAL DISTRESS - Trisandi Eka Putri; Sri Mulyati; Amelia Nurbayanti (JASS (Journal of Accounting for Sustainable Society), 2021)
In this study, the aim of this research is to determine the effect of the ratio of profitability, liquidity, leverage and real interest rate on financial distress in various industrial sector companies listed on the Indonesia Stock Exchange for the period 2017-2019. With this research, it is hoped that it can provide new knowledge related to financial distress in a company. The independent variables used in this study are the ratio of profitability to the proxy of ROA, liquidity with the proxy of the current ratio, leverage with the proxy debt ratio, and the real interest rate. Meanwhile, the dependent variable used is financial distress. The method of measurement in determining financial distress in this study uses the springate method (S-score). The analytical tool in this study using logistic regression analysis. The sample in this study were 37 companies which were taken by purposive sampling technique in a span of 3 years, so that the number of observational data was 111. Based on the results of this study using logistic regression analysis, namely the profitability ratio proxied by ROA partially has a negative and insignificant effect on financial distress, the liquidity ratio proxied by CR partially has a negative and significant effect on financial distress. partial has no positive and significant impact on financial distress, partially real interest rate has a negative and significant effect on financial distress, profitability ratio (ROA), liquidity (current ratio), leverage (debt ratio), and real interest rate simultaneously have a significant effect against financial distress.